Participação Ocupacional de mães com dor lombar nos cuidados com o bebê - Buin, Luciana (2024)
Low back pain is one of the biggest causes of disability in the world, and has a high incidence in women during pregnancy, and may persist in the postpartum period, becoming chronic. Its presence impacts maternal baby care activities; therefore it is important to develop actions that help mothers manage pain and facilitate their routine. The main objective of this research was to understand the role of occupational therapy with mothers with gestational low back pain in their participation in the care of their babies up to two years old to create educational material in the form of an educational booklet. To achieve this, three articulated studies were developed (systematic reviews, Survey research and construction of an educational booklet, validated by a committee of experts). The results of study 1 (reviews) revealed that therapists work in activities of daily living and return to work with pain management and stress management strategies and that low back pain has important impacts on relationships and emotional well-being of pregnant women and postpartum women. In study 2 (Survey), participants indicated that low back pain impacts activities such as putting in and taking out of the crib, carrying and bathing. Based on these results, an educational booklet was created that presents information on gestational low back pain and guidance on pain management and strategies for organizing the environment. This research demonstrates that occupational therapists can contribute positively not only to the management of gestational low back pain, but to the impact of pain in psychosocial contexts, supporting women in their adaptation to the maternal role and helping to build new skills and adjustments in the face of low back pain.